Information Languages of the Automatic Information Retrieval System for Electrochemical and Chemical Coatings - Варнене, Регина; Прокопчик, Мария (Knygotyra, 1985)
The article deals with the problem of information retrieval languages in the automatic information retrieval systems organized in the Institute of Chemistry and Chemical Technology of the Academy of Sciences of Lithuanian SSR.The choice of definite system of information retrieval languages depends on the tasks presented to the system. One of the main demands to the system is the condition of onetime exhaustive input information processing and its use to realize all functions of the system. This request influences the choice of the information retrieval language.The automatic inf. retrieval system is based on the descriptor language without grammar and “Rubricator for electrochemical and chemical coatings”. Each of those two languages may be used autonomously or in combination. The Rubricator’s classification neutralizes the influence of synonymy of the natural language on the indexation and simplifies information retrieval according to the request subject. On the other hand, the use of descriptor language enables deep indexation which makes it possible to decrease the noise and enables information retrieval according to the special request.The following questions are discussed in the item: 1.1. Preliminary information processing; 1.1. Descriptor language; 1.1.1. Primary collection of key-words; 1.1.2. Study of science subject in the Institute; 1.1.3. “Rubricator for electrochemical and chemical coatings”.The document retrieval according to the request will be realized as a dialogue between the system and information users by means of videoterminal.